1951
DOI: 10.1111/j.1398-9995.1951.tb03399.x
|View full text |Cite
|
Sign up to set email alerts
|

On the Pathogenetic Role of Histamine and the Vascular Apparatus in Certain Forms of Headache

Abstract: Headache is merely a symptom, and clinically our efforts should concentrate on tracing the course of the headache in the give case, though often we get no farther than to establish the dynamics of the headache and adopt the treatment accordingly.In a preceding paper (i) it was reported that 63 % of the patients in our neurological clinic complained of headache. About the various forms of headache, among 459 cases of paroxysmal headache migraine occurred in 81 %, allergic headache in 6 %, histamine hemicrania i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

1956
1956
1985
1985

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Most of the larger publications (1,8,11,20,21) show a relatively constant familial occurrence of migraine. There seems to be little doubt that Dalsgaard-Nielsen's (19) statement is the result of the author's rather wide diagnostic criteria at that time, and that K. A. Ekbom's (18) statement is due to the composition of a rather small material.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the larger publications (1,8,11,20,21) show a relatively constant familial occurrence of migraine. There seems to be little doubt that Dalsgaard-Nielsen's (19) statement is the result of the author's rather wide diagnostic criteria at that time, and that K. A. Ekbom's (18) statement is due to the composition of a rather small material.…”
Section: Discussionmentioning
confidence: 99%
“…Information regarding the familial occurrence of migraine among patients with cluster headache varies considerably (Table 4). Dalsgaard-Nielsen (19) found that in 52% of cases there was a familial occurrence of migraine; K. A. Ekbom (18), on the other hand, found that no one had. Most of the larger publications (1,8,11,20,21) show a relatively constant familial occurrence of migraine.…”
Section: Discussionmentioning
confidence: 99%
“…Most workers in the field nowadays, however, are not prepared to identify this substance with histamine. 1,[11][12][13][14][15][16][17] I have found neither the sensitivity test nor the histamine de-sensitization treatment to fulfil their early promise.…”
mentioning
confidence: 99%